MLTI-13. RESPONSE ASSESSMENT OF MELANOMA BRAIN METASTASES TREATED BY STEREOTACTIC RADIOTHERAPY OR IMMUNOTHERAPY OR BOTH: A COMPARISON OF RECIST 1.1, RANO AND iRANO CRITERIA. (12th August 2019) - Le Rhun, Emilie; Wolpert, Fabian; Fialek, Maud; Devos, Patrick; Andratschke, Nicolaus; Reyns, Nicolas; Dummer, Reinhard; Mortier, Laurent; Weller, Michael
Abstract: BACKGROUND: The evaluation of response for brain metastases (BM) may be challenging in the context of treatment by stereotactic radiotherapy (SRT) or immunotherapy or both. METHODS: We reviewed clinical and neuroimaging data of 62 melanoma patients with newly diagnosed BM treated by the combination of immunotherapy and SRT (n=33, group A), immunotherapy alone (n=10, group B) or SRT alone or in combination with other systemic therapies (n=19, group C). Response was assessed using RECIST 1.1, RANO or iRANO criteria. RESULTS: BRAF mutations were noted in 26 patients. 54 patients (87%) had 1–3 metastases. The median DS-GPA was 3. After a median follow-up of 30.5 months, 39 patients have experienced CNS progression, 16 (48.5%) in group A, 9 (90%) in group B, 14 (73.5%) in group C. Median PFS was 129.5 days (range 82–532) in group A, 75 days (range 35–203) in group B, 136 days (range 59–514) in group C. Forty-seven patients (76%) had died at the time of the analysis, 22 (66.5%) in group A, 7 (70%) in group B, 18 (94.5%) in group C. Median OS was 345 days (range 65–1824) in group A, 174.5 days (range 50–1361) in group B, 409 days (range 102–1244) in group C. 52 MRI scans were available for central review: pseudoprogression was documented in 9 patients (29%) in group A, 0 (0%) in group B, 5 (29.5%) in group C. Response rates were similar with all three sets of response criteria. Progressive disease was less often called when applying iRANO to assess SRT target lesions. CONCLUSIONS: Despite the retrospective nature and the small sample size, these data may indicate that the omission of SRT from first-line treatment may compromise outcome. Pseudoprogression is uncommon with immunotherapy alone; pseudoprogression rates were similar after SRT alone or in combination with immunotherapy or other systemic treatment.